Beethoven Festival directed by Felix Weingartner, Paris, May 5, 7, 10, and 12, 1905 - Lalo, Pierre, 1866-1943:::Contributor::::::::::::; Sociéte Musicale G. Astruc & Cie::::::::::::::: (L.-M. Fortin et Cie.; Paris; France, 2020)
Program booklet for the Beethoven festival at the Nouveau-Théatre, Paris, on May 5, 7, 10, 12, 1905, with notes by Pierre Lalo. The festival included all nine Beethoven Symphonies, the Fourth Piano Concerto, the Violin Concerto, "Ah, perfido," op. 65, and the introduction to the second act of Fidelio and Florestan's aria.